Response of Shoot Girdling on Fruiting Characteristics of Litchi Cultivars Grown Under the Sub- Himalayan Terai Region of West Bengal - Subba, Saidiksha; Bhowmick, Nilesh; Chakraborty, Aditi; Medda, Partha Sarathi; Dutta, Puspendu; Ghosh, Arunava (International Journal of Economic Plants, 2022)
Litchi is an important sub-tropical fruit crops of India and grown mainly in Bihar, West Bengal, Uttarakhand, Uttar Pradesh, Punjab, Haryana, Karnataka, Assam and Tripura. It is an essentially sub-tropical fruits and requires seasonal temperature variations for best flowering and fruiting. Girdling is a worldwide practiced for improvement of flowering and fruiting in fruit crops. Even after prolific flowering and fruit set, a heavy flower and fruit drop is a major concern in litchi. Shoot girdling is method of removal of strip of bark approximately 2-5 mm to block or reducing of sap flow through the bark or phloem, to the lower part of the trees or to the roots in order to enhance profuse flowering, fruit weight, size, yield, quality and enhancement of fruit maturity in various fruit crops. An experiment was conducted at the Instructional Farm, Dept. of Pomology and Post Harvest Technology, Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal, India during 2018–2019. The girdling of shoot and its effect on different cultivars were studied with factorial randomized block design having two levels of girdling (without girdling and with 4 cm girdling) and seven levels of cultivars (Calcuttia, Elaichi, Bedana, Bombai, China, Shahi and Muzaffarpur). Results indicated that Calcuttia recorded minimum fruit drop in non girdling (36.70%) and in shoot girdling (11.20%) and also in maximum fruit yield in non girdling (33.15 kg tree-1) as well in shoot girdling (37.21 kg tree-1). judge the effect of girdling on yield attributes of different litchi cultivars